Review of actual risks on aggravating infectious diseases epidemiological situation in the Indo-West-Pacific region important for sanitary protection of the territory of the Russian Federation - Aleksandra V. Ivanova; A. A. Zubova; Zh. A. Kas'jan; L. N. Dmitrieva; E. A. Chumachkova; M. V. Pospelov; A. A. Zimirova; L. D. Shilova; S. A. Jarulina; S. A. Shcherbakova; V. V. Kutyrev (Инфекция и иммунитет)
Here, we review summarized epidemiological data and analyze the situation on infectious diseases in the countries of the Indo-West-Pacific region that require measures for sanitary protection of the territory of the Russian Federation. The main source of relevant information was the official websites and periodicals of the WHO, Ministries of Health of the respective countries. The data from other international organizations (Food and Agriculture Organization of the United Nations, World Organization for Animal Health), electronic aggregators of operational information (ProMED-mail, EpiSouth, arbo-zoonet, etc.), data from articles published in peer-reviewed journals covering epidemiological issues were used. In recent years, due to a set of reasons, the risk of infectious diseases entering Russia from the Indo-West-Pacific region has increased manifold: actively developing tourism to Asian countries, higher number of trade and economic ties, increased number of direct flights with the countries of the region. The paper systematizes data on morbidity and territorial distribution of diseases in the Western Pacific and South-East Asia regions by assessing potential risks for persons visiting it. During the analysis, it has been established that the epidemiological situation currently developing in the Indo-Pacific region poses a significant threat to the sanitary and epidemiological welfare of the population primarily due to the increasing risks for spread of dangerous infectious diseases into the territory of the Russian Federation. The most probable is the risk of spreading of infectious diseases such as cholera, malaria and dengue fever, the unfavorable epidemiological situation on which has developed in recent years in the region. At the same time, the presence of direct transportation links between Russian regions and a number of countries in the region (Thailand, Sri Lanka, Vietnam, Maldives, India, Mongolia, China, Myanmar) multiplies the risk of spreading for such diseases. According to the previously developed methodology for calculating the risk of infectious diseases entering the territory of the Russian Federation, it was established that there is a high risk of dengue fever entry from Laos, Malaysia, Nepal, Thailand and the Philippines.